Neuroprotective Effects of Functionalized Hydrophilic Carbon Clusters: Targeted Therapy of Traumatic Brain Injury in an Open Blast Rat Model - Parasuraman Padmanabhan; Jia Lu; Kian Chye Ng; Dinesh Kumar Srinivasan; Kumar Sundramurthy; Lizanne Greer Nilewski; William K. A. Sikkema; James M. Tour; Thomas A. Kent; Balázs Gulyás; Jan Carlstedt-Duke (Biomedicines)
Traumatic brain injury (TBI) causes multiple cerebrovascular disruptions and oxidative stress. These pathological mechanisms are often accompanied by serious impairment of cerebral blood flow autoregulation and neuronal and glial degeneration. Background/Objectives: Multiple biochemical cascades are triggered by brain damage, resulting in reactive oxygen species production alongside blood loss and hypoxia. However, most currently available early antioxidant therapies lack capacity and hence sufficient efficacy against TBI. The aim of this study was to test a novel catalytic antioxidant nanoparticle to alleviate the damage occurring in blast TBI. Methods: TBI was elicited in an open blast rat model, in which the rats were exposed to the effects of an explosive blast. Key events of the post-traumatic chain in the brain parenchyma were studied using immunohistochemistry. The application of a newly developed biologically compatible catalytic superoxide dismutase mimetic carbon-based nanocluster, a poly-ethylene-glycol-functionalized hydrophilic carbon cluster (PEG-HCC), was tested post-blast to modulate the components of the TBI process. Results: The PEG-HCC was shown to significantly ameliorate neuronal loss in the brain cortex, the dentate gyrus, and hippocampus when administered shortly after the blast. There was also a significant increase in endothelial activity to repair blood–brain barrier damage as well as the modulation of microglial and astrocyte activity and an increase in inducible NO synthase in the cortex. Conclusions: We have demonstrated qualitatively and quantitatively that the previously demonstrated antioxidant properties of PEG-HCCs have a neuroprotective effect after traumatic brain injury following an explosive blast, acting at multiple levels of the pathological chain of events elicited by TBI.